2006
DOI: 10.1007/s00125-006-0509-8
|View full text |Cite
|
Sign up to set email alerts
|

Adult rat liver cells transdifferentiated with lentiviral IPF1 vectors reverse diabetes in mice: an ex vivo gene therapy approach

Abstract: Aims/hypothesis We examined a clinical model of ex vivo transdifferentiation of primary adult hepatocytes to insulinsecreting cells for the treatment of type 1 diabetes. Materials and methods Isolated rat hepatocytes were transduced in primary culture with a human lentivirus containing pancreatic duodenal homeobox 1 (PDX1, now known as insulin promoter factor 1, homeodomain transcription factor [IPF1]). Insulin expression and secretion of the newly engineered cells were assessed in vitro by RT-PCR, in situ hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 48 publications
1
21
1
Order By: Relevance
“…The target cells in these methods mainly focus on hepatic and skeletal muscle cells, but hepatic and skeletal muscle cells are not endocrinal cells, and are quite different from β cells; they usually need to be genetically modified in response to glucose and processing from pro-insulin to insulin. There is a considerable amount of endocrinal cells in gastrointestinal tracts, which are considered ideal target cells in the gene therapy of diabetes [14,15] . Considering these facts, we attempted to transfer the exogenous human insulin gene by gastrointestinal tracts.…”
Section: Introductionmentioning
confidence: 99%
“…The target cells in these methods mainly focus on hepatic and skeletal muscle cells, but hepatic and skeletal muscle cells are not endocrinal cells, and are quite different from β cells; they usually need to be genetically modified in response to glucose and processing from pro-insulin to insulin. There is a considerable amount of endocrinal cells in gastrointestinal tracts, which are considered ideal target cells in the gene therapy of diabetes [14,15] . Considering these facts, we attempted to transfer the exogenous human insulin gene by gastrointestinal tracts.…”
Section: Introductionmentioning
confidence: 99%
“…Our work provides potential novel regulatory elements that should be included when screening for mutations that affect HNF1␣ expression. NKX6.1 is uniquely expressed in mature beta cells of the pancreas (32) but is not expressed in the liver (57). This novel regulatory network may provide potential new targets for diagnosis and MODY and possibly implicate a new gene (NKX6.1) involved in this disease.…”
Section: Nkx61 Regulates Hnf1␣ In Beta Cellsmentioning
confidence: 99%
“…Ferber et al [2000] first reported that transient adenovirus-mediated expression of pancreatic and duodenal homeobox gene 1 (Pdx-1) in hepatocytes activated the expression of endogenous insulin and ameliorated hyperglycemia in diabetic mice treated with streptozotocin (STZ) [Ber et al, 2003]. Recently, reprogramming of a range of liver cell types into pancreatic cells in vitro by forced expression of Pdx-1 has also been reported [Yang et al, 2002;Zalzman et al, 2003Zalzman et al, , 2005Cao et al, 2004;Li et al, 2005;Sapir et al, 2005;Tang et al, 2006a,b;Fodor et al, 2007].…”
mentioning
confidence: 92%